1997
DOI: 10.1046/j.1365-4362.1997.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the clinical presentation and outcome of herpes zoster in a tertiary dermatology outpatient referral clinic

Abstract: Our study indicated that older patients (aged more than 50 years) were at a higher risk of developing post-herpetic neuralgia. They were also more likely to suffer morbidity, e.g. insomnia. There is a need to educate patients at risk to identify the prodrome and skin eruptions of herpes zoster so that early antiviral therapy can be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
3
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 19 publications
4
61
3
7
Order By: Relevance
“…In our study thoracic dermatomal involvement was seen in majority of patients (62%) followed by lumbar (16%) and cranial (12%) and cervical (8%) dermatomes. This is in contrast to the study by Goh and Khoo where the most commonly involved dermatomes were thoracic in 45% and cervical in 23% [9]. In our study multidermatomal involvement was observed in 11 patients and herpeszoster duplex bilateralis and disseminated herpes zoster was observed in one case each ,all of them were immunocompromised.…”
Section: Discussioncontrasting
confidence: 97%
“…In our study thoracic dermatomal involvement was seen in majority of patients (62%) followed by lumbar (16%) and cranial (12%) and cervical (8%) dermatomes. This is in contrast to the study by Goh and Khoo where the most commonly involved dermatomes were thoracic in 45% and cervical in 23% [9]. In our study multidermatomal involvement was observed in 11 patients and herpeszoster duplex bilateralis and disseminated herpes zoster was observed in one case each ,all of them were immunocompromised.…”
Section: Discussioncontrasting
confidence: 97%
“…More than two third of the reported cases occur in individuals over fifty years of age and less than ten percent occur in those under the age of twenty years. The average age at presentation in our study was 29.6 years which is 08 years less than the findings of Dubey Anand Kumar, Jaisainkar TJ and Thappa Devinder Mohan [12] , and about 18 years less than the findings by Goh CL and Khoo L [13] .…”
Section: Discussioncontrasting
confidence: 82%
“…This may be explained by the fact that majority of our OPD patients are in age group of 21-40 years. In our study, thoracic dermatome was involved in 268 (74.44%) cases which is significantly higher than the study conducted by Goh CL & Khoo L [13] , where the involvement was seen only in 45 % of the cases and by Dubey Anand kumar [12] , where the involment was only 54.81% of the cases. Cervical dermatome and ophthalmic nerve involvement in our study was 9.72% and 6.66% of the cases which was slightly less than the study by Dubey Anand Kumar where the inlvolvement of the cervical dermatome and ophthalmic nerve was 15.8% & 9.3 % cases respectively.…”
Section: Discussioncontrasting
confidence: 68%
“…6 However, Goh et al found the mean age of herpes zoster in their study to be 48.8 years and an equal sex ratio of 1:1. 7 Brănişteanu et al found 35% of patients in the 70-80 years age group and female/male ratio of 1.22:1. 4 In this study the male/female ratio was skewed in favour of males at 6.6:1.…”
Section: Discussionmentioning
confidence: 97%
“…6 The dermatomal segments most commonly affected were thoracic (65.4%) followed by cervical (11.9%), cranial (11.5%) and then other segments, similar to the study by Goh et al whereas in the other Indian study, thoracic segments were most common followed by cranial segments. 6,7 Presence of zoster associated pain anytime during the course of the illness in various studies have been reported in 95% and 94.6% of cases. 6,7 However the incidence of zoster associated pain was found to be only 63% in …”
Section: Discussionmentioning
confidence: 99%